DEMO PEMBUATAN COMPOST BIN SEDERHANA KEPADA WARGA DESA ANTIROGO JEMBER GUNA ALTERNATIF PENANGANAN SAMPAH ORGANIK - Ilham Muhklisin; Putri Santika (Bajang Institute, 2023)
Organic household waste accounts for a large portion of Indonesia's waste management problems, especially in the Jember Regency. To overcome this, innovations such as the composting bin are viable for home-scale application. However, this innovation is not widely known by the people. The purpose of this extension activity is to introduce the composting bin to the people of the Antirogo village, Jember district. The counseling method was in the form of a demonstration of handmade aerobic compost. This activity was well received by the community where several households have succeeded in assembling their compost bins.